2020
DOI: 10.1021/acs.jpclett.0c01599
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Bandgap Optical Modulation of Quantum Dot Blinking Statistics

Abstract: Colloidal quantum dots (QDs) suffer from pervasive photoluminescence intermittency that frustrates applications and correlates with irreversible photodegradation. In single-QD spectroscopies, blinking manifests as sporadic switching between ON and OFF states without a characteristic time scale, and the longstanding search for mechanisms has been recently accelerated by techniques to controllably modulate the QD environment. Here, we develop an all-optical modulation scheme and demonstrate that sub-bandgap ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…While the trapped exciton persists, Auger recombination competes with emission and increases the proportion of the off time in the blinking trajectory. There is experimental evidence for both types of blinking mechanisms in semiconductor nanocrystals; in fact, they may operate simultaneously. …”
Section: Introductionmentioning
confidence: 99%
“…While the trapped exciton persists, Auger recombination competes with emission and increases the proportion of the off time in the blinking trajectory. There is experimental evidence for both types of blinking mechanisms in semiconductor nanocrystals; in fact, they may operate simultaneously. …”
Section: Introductionmentioning
confidence: 99%
“…Intensity binning made a huge success in the early endeavors of revealing the complex temporal nature of single QD blinking, and the power-law analysis remains popular among researchers. 15 Because of its popularity, the limitations and drawbacks of intensity binning should be considered with particular caution. First and most obviously, the choice of binning and thresholding could create artifacts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a manifestation of self-similarity behavior that is seen in the blinking of many types of fluorophores 3 , the power-law relationship is highly robust to external perturbations. 3,27,28 A previous study by Hasham et al 29 reported that a sub-bandgap CW laser can change the QD blinking power-law statistics by depleting excited states, resulting in more blinky QDs. In our experiments, we find that the MIR field depletes the OFF states and alters the OFF-time power-law statistics.…”
mentioning
confidence: 99%